Problems of education re-structuring brought up by socially responsible design of policy - Vladimir E. Makarov, Svetlana N. Fomina; Rostovskaya, Tamara K.; Knyazkova, Ekaterina A.; Bereza, Natalia A. (Opción, 2019)
The purpose of this article is to consider the risks of social networks and the possible measures against them via scientific-pedagogical works and theoretical foundations and ideas as a method. As a result, the state youth policy should recognize the primary role of culture in strengthening and multiplying the traditional moral and spiritual values, and in enhancing the unity of multinational peoples of the Russian Federation. As a result, the state should create conditions for expanding the young man's opportunities in choosing his life path, achieving personal success, regardless of his material level and social status.